2008
DOI: 10.1097/ccm.0b013e318186ffe6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of bedside glucose measurement from three glucometers in critically ill patients*

Abstract: Under standardized conditions, glucose results from three point-of-care testing devices were inaccurate in both intensive care unit and non-intensive care unit patients. Among intensive care unit patients, inaccurate glucose readings were most frequently falsely elevated, resulting in misinterpretation of high glucose values with subsequent inappropriate insulin administration or masking of true hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(107 citation statements)
references
References 11 publications
2
97
1
7
Order By: Relevance
“…2 however, the hematocrit range clearly interferes with glycemia results, invalidating point-of-care analysis even with arterial blood in severe anemia. 9,31,44 We agree with hoedemaekers et al 44 that in this situation glycemia is sometimes underestimated, and in our study, the corrective formula provided by Mann et al 31 did not effectively correct underestimation. In severe anemia, a frequent ICU situation associated with blood transfusion recommendations 45 requires alternative glycemia-monitoring methods, primarily better glucometers (ie, gas analyzers or last-generation pOC devices that diminish secondary biases at the hemoglobin range).…”
Section: Acknowledgmentssupporting
confidence: 34%
“…2 however, the hematocrit range clearly interferes with glycemia results, invalidating point-of-care analysis even with arterial blood in severe anemia. 9,31,44 We agree with hoedemaekers et al 44 that in this situation glycemia is sometimes underestimated, and in our study, the corrective formula provided by Mann et al 31 did not effectively correct underestimation. In severe anemia, a frequent ICU situation associated with blood transfusion recommendations 45 requires alternative glycemia-monitoring methods, primarily better glucometers (ie, gas analyzers or last-generation pOC devices that diminish secondary biases at the hemoglobin range).…”
Section: Acknowledgmentssupporting
confidence: 34%
“…Plasma glucose values by capillary point-of-care testing have been found to be potentially inaccurate, with frequent false elevations [479][480][481] over the range of glucose levels, but especially in the hypoglycemic and hyperglycemic ranges [482] and in shock patients (receiving vasopressors) [478,480]. A review of studies found the accuracy of glucose measurements by arterial blood gas analyzers and glucose meters by using arterial blood significantly higher than measurements with glucose meters using capillary blood [480].…”
Section: We Suggest the Use Of Arterial Blood Rather Than Capillary Bmentioning
confidence: 99%
“…While few animal studies have been done, the reliability of CGMSs in critically ill patients is an area of active research. The results to date have revealed a strong correlation between arterial reference blood glucose and better performance, compared with point-of-care devices (Corstjens et al 2006;Hoedemaekers et al 2008;Holzinger et al 2009;Brunner et al 2011). These studies pointed out that the accuracy of CGMSs becomes diminished in the hypoglycaemic range.…”
Section: Discussionmentioning
confidence: 99%